PEMBERDAYAAN MASYARAKAT DESA KARANG MELATI MELALUI PEMBUATAN KEBUN HERBAL KELUARGA - Mardova, Liyana; Firdaus, Thoha; Saputra, Yoga (Universitas Mataram, 2025)
This community service activity was carried out in conjunction with the Community Service Program (KKN) of Universitas Nurul Huda students in Karang Melati Village, Semendawai Timur District, Ogan Komering Ulu Timur Regency. The purpose was to empower the community through the establishment of family herbal gardens (TOGA) as an effort to raise awareness of preventive health and the utilization of home yards. The activity employed a participatory method involving village officials, youth organizations (Karang Taruna), and women’s groups (PKK). The initial stage consisted of socialization on the benefits of herbal plants for health and their economic potential, followed by collective planting of ginger, turmeric, and lemongrass in a designated village area. This planting served as both a symbolic action and an important momentum to foster collective awareness of utilizing local potential. The results showed strong community enthusiasm, indicated by the active involvement of 20 households and increased understanding of the benefits of TOGA. In conclusion, the establishment of family herbal gardens has strengthened mutual cooperation, built health independence, and opened opportunities for developing a community-based herbal economy in Karang Melati Village.